Pemberian Tepung Bawang Dayak (Eleutherine palmifolia) dalam Pakan terhadap Profil Hematologi Darah Puyuh: The Effect of Feeding of Eleutherine palmifolia Meal in Diet on The Hematological Profile of Quail - Haerul, Muhammad; Hermana, Widya; Sumiati (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2024)
The study evaluated the effects of feeding Bawang Dayak (Eleutherine palmifolia) meal in the diet on the hematology profile in quails. A total of 160-layer quails (Coturnix-coturnix japonica strain) aged 8 weeks to 14 weeks were assigned on a completely randomized design (CRD) with 4 treatments, 4 replications with 10 quails per replication. The treatments consisted of R1 = diet control, R2 = diet contained 0.1% Bawang Dayak meal, R3 = diet contained 0.2% Bawang Dayak meal, and R4 = diet contained 0.3% Bawang Dayak meal. The variables observed were the hematology profile quail, including erythrocytes, hemoglobin, leukocytes, hematocrit, lymphocytes, heterophils, eosinophils, monocytes, basophils, and the ratio of heterophils to lymphocytes (H/L). Data were analyzed using analysis of variance (ANOVA), and any significant differences were tested using a post hoc Tukey test. The results showed that the usage of Bawang Dayak meal as a phytobiotic in the diet up to 0.3% did not affect quail blood hematology such as erythrocytes, hemoglobin, leukocytes, hematocrit, leukocyte differentiation and the ratio of H/L. The inclusion of 0.2% Bawang Dayak meal resulted in the H/L ratio being within normal conditions, reflecting its function to maintain stress levels of layer quails. In conclusion, utilization of Bawang Dayak meal in a diet of up to 0.3% does not affect the hematological profile of quail. Key words: bawang dayak, Eleutherine palmifolia, hematology, quail